On the isolation of a MIMO 2 × 2 antenna system using non‐resonant elements: 1.71 GHz–2.69 GHz case study. Issue 9 (September 2017) - Grau, L.; Andújar, A.; Anguera, J.
Abstract: A MIMO antenna system with two non‐resonant antenna elements operating at the high‐bands of LTE (1.71GHz–2.69GHz) is proposed. To improve the isolation, a stub has been located between the two non‐resonant elements in a smartphone platform. Results for measured multiplexing efficiency and isolation are compared with and without the stub. The main conclusion is that the stub not only improves isolation but also improves the average measured multiplexing efficiency by 1dB across the band.